ANALISA EKSTRAK ETIL ASETAT AKAR KAIK-KAIK (Uncaira cordata (Lour.) Merr.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Reza Amelia; Riky; Febri Nur Ngazizah (Journal of Indonesian Medical Laboratory and Science, 2021)
The people of Kalimantan use many herbs for treating diseases, one of them is akar kaik-kaik (Uncaira cordata (Lour.) Merr.) The plant has a high concentration of alkaloids, phenolic, steroids, terpenoids, and flavonoids. that act as antibacterias using diffusion method so the Kirby Bauer/disk paper method used to define antibacterial activity marked the inhibition zone for S. aureus, which is a spherical positive Gram bacterium. U. cordata cordata was extracted through multilateral extraction by n-hexane solution followed by ethyl acetate. The extract used in this study was ethyl acetate with 5 variations of concentration treatment (100 mg/1, 200 mg/1, 300 mg/1, 400 mg/1, 500 mg/1). This research was an experiment design and analyzed by One Way ANOVA test, the mean score for inhibition zone for U. cordata ethyl ecetate extracts in 100 mg/L concentration was 12.7 mm under the weak category, for the concentration of 200 mg/L was 14.2 mm in the weak category, for the concentration of 300 mg/L was 15.3 mm in the weak category, for  the concentration of 400 mg/1 was 16.3 mm in the medium category and for the concentration of 500 mg/1 was 17.7 mm in the medium category.